Herbal medicines adulteration with erectile dysfunction pharmaceuticals in sub-Saharan Africa: call to strengthen regulatory measures - Ouoba, Kampadilemba; Dori, Daniel; Ashie, Adela; Soulama, Issiaka; Semdé, Rasmané (Frontiers in Medicine, 2025)
Sub-Saharan Africa is experiencing record levels of informal use of herbal medicines by the population for primary health care, with prevalence rates of up to 90% in some countries. This situation is linked to the high cost of pharmaceuticals and the popular perception that natural remedies are harmless. Furthermore, the proportion of men suffering from erectile dysfunction in sub-Saharan African countries remains high, varying between 25 and 70%. This dual challenge is at the root of the practice of adulterating herbal medicines with phosphodiesterase 5 inhibitors indicated for the treatment of erectile dysfunction, using abnormally high doses. This fraudulent practice poses a significant threat to consumer health, particularly for patients with comorbidities – potentially fatal erectile dysfunction, serious cardiac side effects, renal or hepatic failure, acute poisoning. This scourge is exacerbated by the weakness of regulatory systems in sub-Saharan African countries, especially their pharmacovigilance systems, which are still generally at low levels of maturity according to the WHO GBT. To combat this scourge, African countries must include the fight against pharmaceutical adulteration of herbal medicines in their policies and regulations on herbal medicines. Through their national regulatory authorities, they must develop and integrate the monitoring of herbal medicines safety into their national pharmacovigilance systems, formally involving herbalists, naturopaths and consumers. They must also develop and implement training programmes for herbalists and naturopaths in good phytotherapy practices, establish appropriate risk communication mechanisms, and ensure regular quality control of so-called natural health products sold on legal and illegal African markets, while tightening sanctions. In short, the fight against counterfeit herbal medicines must be fully integrated into the overall fight against counterfeit medicines in sub-Saharan Africa.